The Application of Good Mining Practice Using Angiospermae Vegetation on Post-Tailing Land at the Mile 21 Research Center, PT. Freeport Indonesia - Sunusi, Widia Anggraeni; Chaerul, Muhammad; Desi, Natsar (ASTONJADRO, 2025)
Sustainable mining requires the implementation of Good Mining Practice (GMP) principles to minimize negative environmental impacts, particularly on tailing disposal sites. One important aspect of GMP is post-mining land rehabilitation, especially on tailing sites that have the potential to cause ecosystem damage. Tailing-affected lands require restoration involving plants capable of adapting to extreme environmental conditions. This study aims to apply GMP by utilizing angiosperm vegetation for land rehabilitation at the Research Center Mile 21, PT. Freeport Indonesia. Tailing-contaminated lands need recovery through plants that can thrive in harsh conditions. Angiosperm plants were selected for their ability to improve soil structure, reduce erosion, and enhance soil fertility. This research evaluates the effectiveness of angiosperm vegetation in accelerating soil recovery and supporting ecosystem sustainability. The findings are expected to provide valuable information and recommendations for more effective tailing site rehabilitation management and serve as a reference for environmentally friendly mining practices in the future.